2014
DOI: 10.1111/nph.12840
|View full text |Cite
|
Sign up to set email alerts
|

Forests trapped in nitrogen limitation – an ecological market perspective on ectomycorrhizal symbiosis

Abstract: Ectomycorrhizal symbiosis is omnipresent in boreal forests, where it is assumed to benefit plant growth. However, experiments show inconsistent benefits for plants and volatility of individual partnerships, which calls for a re-evaluation of the presumed role of this symbiosis.We reconcile these inconsistencies by developing a model that demonstrates how mycorrhizal networking and market mechanisms shape the strategies of individual plants and fungi to promote symbiotic stability at the ecosystem level.The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
169
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(175 citation statements)
references
References 69 publications
3
169
2
1
Order By: Relevance
“…While their secretion appears to be induced by the presence of protein (16), recent results for a model ECM species (Paxillus involutus; Boletales, Basidiomycota) also showed that uptake of N from organic matter is additionally dependent on the availability of a simple carbon (C) source (17). The latter result supports the hypothesis that mining for organic N by ECM species does not occur without an energy supply (18,19). However, since the last two studies compared only the presence and absence of glucose, it has yet to be determined how different levels of C affect organic N degradation.…”
supporting
confidence: 72%
“…While their secretion appears to be induced by the presence of protein (16), recent results for a model ECM species (Paxillus involutus; Boletales, Basidiomycota) also showed that uptake of N from organic matter is additionally dependent on the availability of a simple carbon (C) source (17). The latter result supports the hypothesis that mining for organic N by ECM species does not occur without an energy supply (18,19). However, since the last two studies compared only the presence and absence of glucose, it has yet to be determined how different levels of C affect organic N degradation.…”
supporting
confidence: 72%
“…Asymbiotic forms of BNF include plant-associated BNF (N-fixing microbes inhabiting the plant rhizosphere but not entering direct plantmicrobe symbioses), as well as heterotrophic BNF carried out by free-living bacteria. Furthermore, BNF from mycorrhizal fungi (Franklin et al, 2014) and cryptogamic communities (Elbert et al, 2012) has been shown to be of significant magnitude. These groups of N fixing organisms are phylogenetically diverse and poorly understood (Vitousek et al, 2013), making the quantification of global BNF rates challenging.…”
Section: Introductionmentioning
confidence: 99%
“…A previous CoupModel application by Wu et al (2012) demonstrated that the nonlim approach could possibly describe short-term C and water dynamics for a Finnish forest site. The same nonlim approach was also used in Franklin et al (2014) to simulate Swedish forest biomass growth and its competition with ECM. This seems to suggest that plant growth and the C cycle can be simulated reasonably with the nonlim approach, although a slight trend of overestimation is exhibited.…”
Section: Comparison Of the Three Ecm Modeling Approachesmentioning
confidence: 99%
“…The ECM implicit approach has been used in a similar way by Kirschbaum and Paul (2002) and Svensson et al (2008a). The nonlim approach assumes an "open" N cycle and plant growth is limited by a constant N availability to a static fixed level (e.g., in Franklin et al, 2014). These three ECM modeling approaches constitute most of the current ECM representations in ecosystem models and are tested by four forest sites situated along a climate and N fertility gradient across Sweden (Fig.…”
Section: Introductionmentioning
confidence: 99%